Electronic clinical records in primary care for estimating disease burden and management. An example of COPD - Luis Verde-Remeseiro; Estrella López-Pardo; Alberto Ruano-Ravina; Francisco Gude-Sampedro; Ramón Castro-Calvo (Elsevier, 2015)
Chronic obstructive pulmonary disease (COPD) is a significant health problem in developed countries. We aimed to estimate the prevalence of COPD in a single Spanish healthcare area. We also aimed to assess if there are any differences in prevalence and spirometry use among primary care services by utilizing already registered information. We designed a cross-sectional study to determine the prevalence of COPD and the performance of spirometries in each primary care service. A total of 8,444 patients were diagnosed with COPD, with a prevalence of 2.6% for individuals older than 39 years. The prevalence increased with age and was much higher in men. Significant heterogeneity was found in the prevalence of COPD and spirometry use among primary care services. COPD was underdiagnosed and there was wide variability in spirometry use in our area. Greater efforts are needed to diagnose COPD in order to improve its clinical outcomes and to refine registries so that they can be used as reliable sources of information